Mutational analysis of the human factor IX promoter : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Genetics at Massey University - Manttan, Jacqueline Elizabeth (Massey University, 1998)
Haemophilia B is a rare congenital bleeding disorder that affects 1 in 30,000 males. It is caused by a functional deficiency in the blood coagulation protein, factor IX, which is expressed primarily within the liver. Patients suffering from the Haemophilia B Leyden phenotype show a distinct pattern of factor IX expression that is characterised by severe to moderate haemophilia within children, which gradually ameliorates after puberty. Such deficiencies in factor IX are created by mutations that occur within the -22 to +13 region of the factor IX promoter. These mutations are responsible for down-regulating factor IX transcription leading to factor IX deficiency by disrupting the binding sites of transcription factors critical for factor IX gene expression. Three specific transcription factors. C/EBP, DBP and HNF4 are thought to be required for constitutive promoter expression. The aim of this thesis was to analyse the roles of these three transcription factors in the regulation of the factor IX promoter. The current studies were focused on two regions (-220 to -202 and +20 to +45) of the factor IX promoter which have been implicated in transcriptional activation. Reporter gene assays using the human hepatoma cell line, Alexander, were carried out on both normal and mutant promoter constructs. Recognition sites for each of the three transcription factors were disrupted by oligonucleotide-directed PCR mutagenesis. The mutated promoter inserts were subsequently inserted into the luciferase reporter gene expression vector, pGL2 Basic (Promega). These constructs were then expressed within the Alexander cell line to compare the extent of transcriptional disruption created by each mutation. EMSA studies were also used to analyse the binding ability of the HNF4 transcription factor to the -6 region of the factor IX promoter. Mutations within the -220 to +45 region of the factor IX promoter downregulated transcription from the promoter to different extents. This suggested that each transcription factor may play a different role in regulating the factor IX promoter. An increase in promoter expression observed with mutant constructs in the presence of exogenous HNF4 confirmed previous experiments which suggested that the HNF4 transcription factor could also act as an activator of promoter expression. Furthermore, the transactivation of the promoter constructs containing a mutation within the main HNF4 site at region -15 to -30 with exogenous HNF4, indicated that a second HNF4 site may be present within the factor IX promoter.
Keywords: Genetic aspects; Hemophilia; Mutagenesis